자생 중나리 종자의 콜히친 처리에 따른 변이체 특성 - 서종택(Jong-Taek Suh); 조광수(Kwang-Soo Cho); 양미희(Mi-Hee Yang); 홍수영(Su-Young Hong) (Weon'ye gwahag gi'sulji, 2005)
본 연구는 자생중나리의 초형이나 화색 및 화형의 돌연변이체를 만들어 육종소재로서 이용하고자 종자에 콜히친으로 처리하였으며 이때 농도는 10, 20, 30mgL-1로 하고 각각 12, 24, 48시간 처리하였다. 포장에서 육안으로 농도 20mgL-1에 24시간 처리구에서 정상적인 중나리와는 달리 잎에 흰색무늬가 양쪽에 3/5이 들어있는 돌연변이체를 선발하였다. 초장, 엽수, 엽폭 등은 정상개체보다 돌연변이체가 작았으나 엽장은 정상개체 7.6cm보다 돌연변이체가 11.8cm로 더 길었다. 공변세포 크기에 있어서도 돌연변이체가 길이 99.66um, 폭 60.8um, 면적 5,097um2로 정상개체(69.8um, 44.7um, 2,665um2)보다 크게 나타났다. 염색체 수는 돌연변이체와 정상개체가 2n=24로 같았다. This study was conducted to produce the mutant plant from wild Lilium leichtlinii native to Korea. To get the new plant, the seeds of wild Lilium leichtlinii were treated by colchicine as concentrations of 10, 20, and 30 mgL-1, and also soaked for 12, 24 and 48 hours, respectively. A marginally variegated mutant with better ornamental value was selected by colchicine treatment soaked for 24 hours, 20 mgL-1 concentration to wild Lilium leichtlinii seeds. The mutant was partly albino in leaf rims. The color of a leaf in mutant consisted with 3/5 white and 2/5 green. Plant height, leaf number and leaf width of mutant was 76.5, 33.3, and 0.73 cm, respectively. But those in normal plants were 96.0, 39.0, and 0.80 cm, respectively. However, the length of leaf in mutant was 11.8 cm longer than that of normal plant 7.6 cm. And the size of guard cells in mutant was 5,097 um2 per cell twice larger than that of normal plants 2,665 um2 per cell. KCI Citation Count: 2